Are Damage Modes Related to Microstructure and Material Loss in Severely Damaged CoCrMo Femoral Heads?. Issue 9 (September 2021) - McCarthy, Stephanie M.; Hall, Deborah J.; Mathew, Mathew T.; Jacobs, Joshua J.; Lundberg, Hannah J.; Pourzal, Robin
Abstract: Background: Fretting and corrosion in metal-on-polyethylene total hip arthoplasty (THA) modular junctions can cause adverse tissue reactions that are responsible for 2% to 5% of revision surgeries. Damage within cobalt-chromium-molybdenum (CoCrMo) alloy femoral heads can progress chemically and mechanically, leading to damage modes such as column damage, imprinting, and uniform fretting damage. At present, it is unclear which of these damage modes are most detrimental and how they may be linked to implant alloy metallurgy. The alloy microstructure exhibits microstructural features such as grain boundaries, hard phases, and segregation bands, which may enable different damage modes, higher material loss, and the potential risk of adverse local tissue reactions. Questions/purposes: In this study, we asked: (1) How prevalent is chemically dominated column damage compared with mechanically dominated damage modes in severely damaged metal-on-polyethylene THA femoral heads made from wrought CoCrMo alloy? (2) Is material loss greater in femoral heads that underwent column damage? (3) Do material loss and the presence of column damage depend on alloy microstructure as characterized by grain size, hard phase content, and/or banding? Methods: Surgically retrieved wrought CoCrMo modular femoral heads removed between June 2004 and June 2019 were scored using a modified version of the Goldberg visually based scoring system. Of the total 1002 heads retrieved over this period, 19% (190 of 1002) were identified as severely damaged, exhibiting large areas of fretting scars, black debris, pits, and/or etch marks. Of these, 43% (81 of 190) were excluded for metal-on-metal articulations, alternate designs (such as bipolar, dual-mobility, hemiarthroplasty, metal adaptor sleeves), or previous sectioning of the implant for past studies. One sample was excluded retroactively as metallurgical analysis revealed that it was made of cast alloy, yielding a total of 108 for further analysis. Information on patient age (57 ± 11 years) and sex (56% [61 of 108] were males), reason for removal, implant time in situ (99 ± 78 months), implant manufacturer, head size, and the CoCrMo or titanium-based stem alloy pairing were collected. Damage modes and volumetric material loss within the head tapers were identified using an optical coordinate measuring machine. Samples were categorized by damage mode groups by column damage, imprinting, a combination of column damage and imprinting, or uniform fretting. Metallurgical samples were processed to identify microstructural characteristics of grain size, hard phase content, and banding. Nonparametric Mann-Whitney U and Kruskal-Wallis statistical tests were used to examine volumetric material loss compared with damage mode and microstructural features, and linear regression was performed to correlate patient- and manufacturer-specific factors with volumetric material loss. Results: Chemically driven column damage was seen in 48% (52 of 108) of femoral heads, with 34% (37 of 108) exhibiting a combination of column damage and imprinting, 12% (13 of 108) of heads displaying column damage and uniform fretting, and 2% (2 of 108) exhibiting such widespread column damage that potentially underlying mechanical damage modes could not be verified. Implants with column damage showed greater material loss than those with mechanically driven damage alone, with median (range) values of 1.2 mm 3 (0.2 to 11.7) versus 0.6 mm 3 (0 to 20.7; p = 0.03). Median (range) volume loss across all femoral heads was 0.9 mm 3 (0 to 20.7). Time in situ, contact area, patient age, sex, head size, manufacturer, and stem alloy type were not associated with volumetric material loss. Banding of the alloy microstructure, with a median (range) material loss of 1.1 mm 3 (0 to 20.7), was associated with five times higher material loss compared with those with a homogeneous microstructure, which had a volume loss of 0.2 mm 3 (0 to 4.1; p = 0.02). Hard phase content and grain size showed no correlation with material loss. Conclusion: Chemically dominated column damage was a clear indicator of greater volume loss in this study sample of 108 severely damaged heads. Volumetric material loss strongly depended on banding (microstructural segregations) within the alloy. Banding of the wrought CoCrMo microstructure should be avoided during the manufacturing process to reduce volumetric material loss and the release of corrosion products to the periprosthetic tissue. Clinical Relevance: Approximately 30% of THAs rely on wrought CoCrMo femoral heads. Most femoral heads in this study exhibited a banded microstructure that was associated with larger material loss and the occurrence of chemically dominated column damage. This study suggests that elimination of banding from the alloy could substantially reduce the release of implant debris in vivo, which could potentially also reduce the risk of adverse local tissue reactions to implant debris.